2004
DOI: 10.1046/j.1365-2702.2003.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephrology nursing: blurring the boundaries: the reality of expert practice

Abstract: There are some nephrology nurses who have sufficient knowledge and experience to prescribe some medications and to order certain investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
0
22
0
1
Order By: Relevance
“…As such, boundaries between doctors who provide medical diagnoses and prescribe medical treatment and nurses as healthcare professionals who carry out orders and implement interventions ordered by doctors are becoming less clear [56]. Blurred boundaries between nurses and physicians leading to DOI: 10.9790/1959-0603014560 www.iosrjournals.org 57 | Page role conflict have been attributed to senior-level nurses, considered as experts in their specialties, who fail to operate within the boundaries of nursing practice [57]. Furthermore, an exploratory study conducted among anesthesiologists and certified registered nurse anesthetists (CRNAs) revealed that conflict among these highlyinterdependent members of the health care team results from divergent views as to who has the responsibility to perform a certain role [25].…”
Section: Discussionmentioning
confidence: 99%
“…As such, boundaries between doctors who provide medical diagnoses and prescribe medical treatment and nurses as healthcare professionals who carry out orders and implement interventions ordered by doctors are becoming less clear [56]. Blurred boundaries between nurses and physicians leading to DOI: 10.9790/1959-0603014560 www.iosrjournals.org 57 | Page role conflict have been attributed to senior-level nurses, considered as experts in their specialties, who fail to operate within the boundaries of nursing practice [57]. Furthermore, an exploratory study conducted among anesthesiologists and certified registered nurse anesthetists (CRNAs) revealed that conflict among these highlyinterdependent members of the health care team results from divergent views as to who has the responsibility to perform a certain role [25].…”
Section: Discussionmentioning
confidence: 99%
“…2008). Bonner and Walker (2004) described the formal boundaries between professionals as defined by the law and informal boundaries, which are created by convention and tradition (Bonner & Walker 2004).…”
Section: Discussion – Reconceptualising a Model Of Rural Practicementioning
confidence: 99%
“…Role blurring between nursing and medicine has been studied in the context of emergency care, nephrology and rural health care (Hegney 1996, Blue 2002, Bonner & Walker 2004, Norris & Melby 2006). There is general agreement that role blurring between these advanced nursing roles and medicine is an inevitable part of health service changes and other pressures in society.…”
Section: Discussion – Reconceptualising a Model Of Rural Practicementioning
confidence: 99%
“…Moreover, the advanced nurse practitioner role within nephrology has been shown to improve the efficiency of patient care, by spending quality time with patients, providing continuity of care and enhanced communication between dialysis team members (Harwood et al 2004). Other aspects of the advanced practitioner role include the insertion and removal of central venous catheters or prescribing/titrating medication doses (Casey 2001; Bonner & Walker 2004). Nursing is changing rapidly, providing the scope for nurses to develop their roles, taking on more advanced activities and interventions to fit the needs of the patients and service demands (Lockhart 2008).…”
Section: Why Is Measuring Key Nephrology Nursing Interventions Indicamentioning
confidence: 99%